Coriolis effects on wind-driven upwelling in enclosed basins. (1st March 2023) - Ito, Wataru; Nakayama, Keisuke; Shintani, Tetsuya
Abstract: Previous studies showed that the smaller the Coriolis parameter, the greater the upwelling that occurs in enclosed basins. This suggests that the Coriolis force suppresses the upwelling, but this has not been confirmed. Therefore, this study aims to clarify the Coriolis effect on upwelling using a three-dimensional hydrodynamic model. We used six different Rossby radius conditions for a two-layer fluid in a rectangular basin to investigate the relative importance of the Coriolis on upwelling. We found that, as expected, the effective upwelling area at the water surface was highest without the Coriolis. The same trend was also observed for a three-layer fluid in a rectangular basin. The theoretical analysis revealed that a geostrophic jet induced by the geostrophic balance along the lateral boundary suppresses the upwelling. Graphical abstract: Image 1 Highlights: Upwelling area decreases with increasing the Coriolis force in a rectangular basin. A geostrophic jet occurs when the Wedderburn Number is on the order of 1. A geostrophic jet suppresses the upwelling. Internal Kelvin and Poincare waves do not influence the upwelling event. The Ekman pumping does not influence a geostrophic jet.